2020
DOI: 10.1126/sciadv.aba1323
|View full text |Cite
|
Sign up to set email alerts
|

Future precipitation increase from very high resolution ensemble downscaling of extreme atmospheric river storms in California

Abstract: Precipitation extremes will likely intensify under climate change. However, much uncertainty surrounds intensification of high-magnitude events that are often inadequately resolved by global climate models. In this analysis, we develop a framework involving targeted dynamical downscaling of historical and future extreme precipitation events produced by a large ensemble of a global climate model. This framework is applied to extreme “atmospheric river” storms in California. We find a substantial (10 to 40%) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 59 publications
7
86
0
2
Order By: Relevance
“…Our future projections of WAFR provide clear evidence that increases in high-magnitude-flows are highly likely under climate change in California ( Fig. 1 ), as supported by previous studies reporting substantial and robust increases in projected extreme precipitation ( 23 , 31 ) and streamflow ( 16 , 19 , 20 ). Earlier snowmelt and larger increases in rain-on-snow events also contribute to more extreme streamflow ( 32 ), implying higher WAFR under climate change.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our future projections of WAFR provide clear evidence that increases in high-magnitude-flows are highly likely under climate change in California ( Fig. 1 ), as supported by previous studies reporting substantial and robust increases in projected extreme precipitation ( 23 , 31 ) and streamflow ( 16 , 19 , 20 ). Earlier snowmelt and larger increases in rain-on-snow events also contribute to more extreme streamflow ( 32 ), implying higher WAFR under climate change.…”
Section: Discussionsupporting
confidence: 84%
“…In California, there is high confidence that projected mountain system recharge will decline in a warming climate due to the loss of the winter snowpack ( 49 ) and shifts from snow to rain ( 32 ), which increases the likelihood of surface runoff rather than percolation. Diffuse and focused recharge may decrease in Southern California due to combined effects of decreasing precipitation and increasing temperature, but their changing directions are not clear in Northern California, given that extreme precipitation will largely increase in future climates ( 9 , 21 , 23 , 31 ). It is also challenging to quantify projected changes in irrigation recharge ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to precipitation, surface wind impacts have received relatively little attention in the AR literature. Strong AR surface winds can damage trees and infrastructure, resulting in economic damages (Huang, Swain, & Hall, 2020; Waliser & Guan, 2017). In their global evaluation, Waliser and Guan (2017) showed that ARs are associated with wind extremes in many regions.…”
Section: Introductionmentioning
confidence: 99%
“…Although projected globally averaged increases in precipitation extremes are quite robust, regional variations are typically substantial. Landfalling precipitation varies strongly due to both topographic influences and mesoscale atmospheric dynamical processes (Huang, Swain, Walton, et al, 2020; Leung et al, 2013; Pontoppidan et al, 2017; Rotunno & Houze, 2007).…”
Section: Introductionmentioning
confidence: 99%